Optimal Expectations and Limited Medical Testing: Evidence from Huntington Disease: Corrigendum - Oster, Emily; Shoulson, Ira; Dorsey, E. Ray (American Economic Review, 2016)
The purpose of this document is to update and correct Figure 4 from "Optimal Expectations and Limited Medical Testing: Evidence from Huntington Disease" (Oster, Shoulson, and Dorsey 2013). This figure documents how perceptions about the risk of HD evolve with symptoms. It compares these perceptions with the "actual risk" of HD based on a Bayesian updating calculation described in the paper. The construction of Figure 4 is correctly described in the text of the paper and the data on perceptions are documented correctly. However, the construction of the "actual risk" series is not accurate. There are two central issues. First, there were data limitations at the time of publication which have since been relaxed and the better data now available changes the picture. Second, there was an error in the construction of Figure 4 which should have been recognized at the time. We detail the issues here and include the corrected figure. The original figure showed evidence of overoptimism at all levels of motor score. The corrected figure shows that for low symptom levels individuals are correct about their risk level, whereas those with more advanced symptoms are overly optimistic. Overall, the levels of overoptimism are lower than documented originally. We will briefly discuss the implications for the theory at the end of this document.